Understanding role of HR in developing successful strategic alliance: Case Study of Automotive Sector - Ullah, Naqeeb; Ijaz, Aamir; Ullah, Aziz; Nawaz, Adil
Human Resource (HR) managers tends to have the significant impact on the organisation activities and resource allocation. The business decisions are also affected by the HR manager activities and capabilities. Therefore, the current study aims to identify the impact of the HR in developing successful strategic alliance using the case of the automotive sector of Pakistan. The research is conducted using the quantitative research design. The data for the study was collected using the questionnaire survey based on the 5-point Likert Scale. The sample of the study included 100 HR managers of the automotive sector of Pakistan. The variables used for elaborating HR role were organisation culture, communication skills and leadership style. The collected data was analysed using descriptive statistics, correlation analysis and regression analysis using SPSS software. The findings of the study have revealed that organisation culture tends to have the insignificant impact on the successful strategic alliance. Furthermore, effective communication skills and leadership styles have the significant impact on successful strategic alliance. The future studies can include indirect variables in the study that can impact on the relationship between the variables investigated in this research. Furthermore, mixed research design can also help future studies to gain comprehensive understanding and knowledge.